Conducting Qualitative Research Online: Challenges and Solutions - Carter, Stacy M.; Shih, Patti; Williams, Jane; Degeling, Chris; Mooney-Somers, Julie (The patient : patient-centered outcomes research, 2021)
What ways of thinking and concrete strategies can assist qualitative health researchers to transition their research practice to online environments? We propose that researchers should foreground inclusion when designing online qualitative research, and suggest ethical, technological and social adaptations required to move data collection online. Existing research shows that this move can aid in meeting recruitment targets, but can also reduce the richness of the data generated, as well as how much participants enjoy participating, and the ability to achieve consensus in groups. Mindful and consultative choices are required to prevent these problems. To adapt to ethical challenges, researchers should especially consider participant privacy, and ways to build rapport and show appropriate care for participants, including protocols for dealing with distress or disengagement, managing data, and supporting consent. To adapt to technological challenges, research plans should choose between online modalities and platforms based on a clear understanding of their particular affordances and the implications of these. Finally, successful research in virtual social environments requires new protocols for engagement before data collection, attention to group numbers and dynamics, altered moderator teams and roles, and new logistical tasks for researchers. The increasing centrality of online environments to everyday life is driving traditional qualitative research methods to online environments and generating new qualitative research methods that respond to the particularities of online worlds. With strong design principles and attention to ethical, technical and social challenges, online methods can make a significant contribution to qualitative research in health.